Župani - simbol slovenske lokalne samouprave in demokracije - Granda, Stane (Studia Historica Slovenica, 2017)
It is the intention of this piece to present the position and function of the mayor throughout the period of Slovenian history from the year 777, when the oldest functionary of our local self-governance was appointed, all the way to modern times or until 1993, when the independent state of Slovenia once again reinstituted the position of the mayor with laws regarding local self-governance. In this the author finds that the Austrian government was more in favour of local self-governance than both Jugoslav regimes, where form, if there was any to begin with, prevailed over content. Of course, mayoral elections were always greatly influenced by economic and internal political situation on the local level.
Keywords: demokracija; lokalna samouprava; Slovenija; zgodovina; župani